Social Reflection in Indian English Literature - Sachin S. Magadum (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Indian English literature, since its inception during the colonial period, has served as a mirror reflecting the nation’s social realities, struggles, and transformations. From colonial subjugation to post-independence reconstruction and globalization, Indian English writers have persistently engaged with issues such as caste, class, gender, identity, and cultural hybridity. This paper explores how Indian English literature has evolved as a tool of social reflection portraying the complexities of Indian society and questioning its socio-political and moral frameworks. The study highlights the works of major authors such as R.K. Narayan, Mulk Raj Anand, Raja Rao, Salman Rushdie, Arundhati Roy, and others, who have contributed to shaping the social consciousness of India through literature.